CODE-SWITCHING PRACTICES IN BILINGUAL CLASSROOM INTERACTION: A SOCIOLINGUISTIC ANALYSIS OF PEDAGOGICAL AND IDENTITY FUNCTIONS - Fakhrul Rijal; Zaki Al Fuad (Sensei International Journal of Education and Linguistic, 2023)
Code-switching is a common communicative practice in bilingual classrooms, particularly in contexts where teachers and students share more than one linguistic repertoire. Although code-switching is sometimes viewed as a sign of linguistic deficiency or lack of target language exposure, sociolinguistic perspectives understand it as a meaningful interactional resource that can support explanation, classroom management, identity negotiation, and participation. This study aims to analyze code-switching practices in bilingual classroom interaction and to examine their pedagogical and sociolinguistic functions. A qualitative classroom discourse study was conducted in three bilingual secondary classrooms. Data were collected through classroom observations, audio-video recordings, teacher interviews, student focus group discussions, and field notes. The data were analyzed using interactional sociolinguistic analysis and thematic coding. The findings revealed that code-switching occurred in three major patterns: inter-sentential switching, intra-sentential switching, and tag switching. The functions of code-switching included clarifying academic content, managing classroom interaction, scaffolding students' comprehension, emphasizing key concepts, building interpersonal solidarity, and negotiating bilingual identity. The findings also showed that students perceived teacher code-switching positively when it helped them understand difficult concepts, but they were less supportive when switching reduced opportunities to use the target language. The study concludes that code-switching should not be treated as random language alternation but as a strategic sociolinguistic practice that requires pedagogical awareness, functional control, and balanced target language exposure.